Outcomes of Advance Care Planning in Dementia Patients Receiving Palliative Care - Siriket, Rattanaporn; Ngamsit, Teerasak; Buabanbut, Rattanawadi; Piasupun, Parichart; Pairojkul, Srivieng (Srinagarind Medical Journal, 2023)
Background and Objectives: Dementia is fatal disease and becomes burden due to increased elderly population. Karunruk Palliative Care Center has established a care program for late-stage dementia. Family education on disease trajectory and established advance care plan (ACP) Methods: A retrospective descriptive study of medical records, care records. Profiles of 65 patients recruited from October 1, 2020 to September 30, 2022. Descriptive statistic, mean, percentage, were used for data analysis. Results: Only 7/65 (10.76%) had an ACP before referral. All patients in our program had an ACP. Place of death of 30 patients were 43.33% at home, 43.33% at Palliative unit, 3.34 % at medical ward, and 3.34% at nursing home. Conclusion: The patient preferences in our program were well respected.